Pathways for Improved Nutrition: a Review of Bangladesh's Agri-Food System Policies - Mizan, Arefin; Roy, Prantik; Hasan, A M Rumayan; Keya, Arfina; Sinha, Ronjini; Rasheed, Sabrina (WorldFish, 2024)
This policy brief examines the extent to which these policies align with the National Nutrition Policy 2015, focusing on their potential to contribute to nutrition-sensitive interventions. By reviewing sectoral policies across agriculture, fisheries, and livestock, this analysis seeks to highlight the strengths and gaps within the current policy framework and to identify opportunities for enhancing the coherence and integration of nutrition-sensitive goals.